“I vouch for it with my name.” The influence of brand perception of family businesses on their credibility and the purchase intention of consumers - Schramm, Holger; Zinser, Anna (Frontiers in Communication, 2025)
Companies that are family-owned consciously use their family background in marketing communications. Nevertheless, the cause-and-effect mechanisms in the processing of such communication have not yet been investigated. In a two-level between-subjects experiment, we examined the influence of brand origin (family vs. non-family business) on brand credibility and consumers' purchase intention. The results show that brands from family businesses are perceived as more sincere and reliable and, consequently, more credible than brands from non-family businesses. This has a positive effect on attitude toward the brand and increases consumers' purchase intention. The study's findings have valuable implications for research and practice.